Dual-colour (near-infrared/visible) emitting annexin V for fluorescence imaging of tumour cell apoptosis in vitro and in vivo. Issue 63 (16th October 2020) - Tsuboi, Setsuko; Jin, Takashi
Abstract : Indocyanine green labeled recombinant annexin V probes (ICG–EGFP–Annexin V and ICG–mPlum–Annexin V) were synthesized for near-infrared and visible fluorescence imaging of tumor cell apoptosis both in vitro and in vivo. Abstract : Indocyanine green (ICG) labelled recombinant annexin V proteins (ICG–EGFP–Annexin V and ICG–mPlum–Annexin V) were synthesized for dual-colour fluorescence imaging of tumour cell apoptosis in vitro and in vivo . The ICG-labelled fluorescent annexin V proteins showed dual (near-infrared and visible) fluorescence emissions with binding ability to phosphatidylserines on the plasma membranes of apoptotic cells. Although several types of fluorescence labelled annexin V ( e.g. FITC–annexin V, Cy3- and Cy5-annexin V) have been reported, there are no dual-colour (near-infrared/visible) emitting apoptosis-detection probes which can be used in vitro and in vivo . In this paper, the utilities of the dual-colour fluorescent annexin V are demonstrated for in vitro and in vivo fluorescence imaging of the apoptosis of human breast tumour cells induced by an antibody–drug conjugate, Kadcyla. The results suggest that the present annexin V probes will be useful to visualize the action of anti-cancer drugs against tumours both at the cellular and whole-body level.